A template-assisted self-organization process for the formation of a linear arrangement of pairs of metallic tips. Issue 1663 (28th February 2014) - Brassat, Katharina; Lindner, Jörg K.N.
ABSTRACT: A novel process for the formation of pairs of opposing metallic nanotips within linear trenches on a silicon wafer is investigated in detail. The process is based on a spreading knife technique typically used in nanosphere lithography to generate monolayers of colloidal polystyrene beads. Here it is applied to initiate self-assembly of spheres in long linear trenches acting as a template for the sphere arrangement. The optimum blade velocity to deposit the spheres selectively and densely packed in the trench depends on the trench surface fraction and can be described by a modified Dimitrov model. It is demonstrated that the spheres can be used as a shadow mask to deposit metallic nanotips in a channel, which are electrically interconnected on each side of the trench, possibly enabling the control and manipulation of nanoobjects in the channel.